Oil palm development and forced displacement in Colombia: Causal or spurious? (2017)
This article analyses whether forced displacement in the Magdalena Department (Colombia) between 2000-2010 was caused not only by the intensity of the armed conflict but also by the growth of the palm agribusiness. We find that a seven percentage point increase in the area used to produce palm per municipality caused an increase of a third of a standard deviation in the rate of forced displacement. These calculations were made on average and after controlling for armed conflict. We rationalize this finding by the fact that the development of the palm oil agribusiness caused displacement due to its land-intensive technology, increasing international prices combined with government subsidies, and the process was aided by paramilitary activities in the region.